2020
DOI: 10.15252/embj.2019104273
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of the PIF7‐HFR1 transcriptional module activity controls plant shade adaptation

Abstract: Shade caused by the proximity of neighboring vegetation triggers a set of acclimation responses to either avoid or tolerate shade. Comparative analyses between the shade-avoider Arabidopsis thaliana and the shade-tolerant Cardamine hirsuta revealed a role for the atypical basic-helix-loop-helix LONG HYPOCOTYL IN FR 1 (HFR1) in maintaining the shade tolerance in C. hirsuta, inhibiting hypocotyl elongation in shade and constraining expression profile of shade-induced genes. We showed that C. hirsuta HFR1 protein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 58 publications
2
40
1
Order By: Relevance
“…Consistent with the RNA-seq data, the transcript level of these genes was upregulated in response to high ambient temperature and correlated with thermomorphogensis as previously shown [ 15 , 29 , 30 ]. Interestingly, the transcript level of LONG HYPOCOTYL IN FAR-RED 1 ( HFR1 ) and PIF3-LIKE 1 ( PIL1 ), which are known inhibitors of PIFs in photomorphogenesis, thermomorphogenesis and shade avoidance responses [ 41 46 ], were up-regulated in the absence of HECs ( Fig 3F ). These data suggest that similar to HEC1 and HEC2 , genes encoding the inhibitors of PIFs are also induced under high ambient temperature responses and perhaps participate in the negative feedback loop to regulate PIF level and activity at high ambient temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the RNA-seq data, the transcript level of these genes was upregulated in response to high ambient temperature and correlated with thermomorphogensis as previously shown [ 15 , 29 , 30 ]. Interestingly, the transcript level of LONG HYPOCOTYL IN FAR-RED 1 ( HFR1 ) and PIF3-LIKE 1 ( PIL1 ), which are known inhibitors of PIFs in photomorphogenesis, thermomorphogenesis and shade avoidance responses [ 41 46 ], were up-regulated in the absence of HECs ( Fig 3F ). These data suggest that similar to HEC1 and HEC2 , genes encoding the inhibitors of PIFs are also induced under high ambient temperature responses and perhaps participate in the negative feedback loop to regulate PIF level and activity at high ambient temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the RNA-seq data, the transcript level of these genes was upregulated in response to high ambient temperature and correlated with thermomorphogensis as previously shown (Hayes et al , 2017; Ma et al , 2016; Sun et al , 2012). Interestingly, the transcript level of LONG HYPOCOTYL IN FAR-RED 1 ( HFR1 ) and PIF3-LIKE 1 ( PIL1 ), which are known inhibitors of PIFs in photomorphogenesis, thermomorphogenesis and shade avoidance responses (Foreman et al , 2011; Hornitschek et al , 2009; Luo et al , 2014; Paulišić et al , 2020; Tavridou et al , 2020; Xu et al , 2017), were up-regulated in the absence of HECs (Fig. 5F).…”
Section: Resultsmentioning
confidence: 99%
“…AtPIF7 has been shown to bind to PHYB (Leivar et al, 2008) and to have a role in promoting Arabidopsis hypocotyls as a result of shade and warm temperature treatments (Li et al, 2012; Fiorucci et al, 2020). Considering that in A. thaliana a functional AtPAR1 binds in vivo to PIFs and other bHLH proteins in the nucleus (Hao et al, 2012; Cifuentes-Esquivel et al, 2013; Paulišić et al, 2021), we aimed to determine whether the DcPAR1 protein is nuclear and capable of heterodimerizing with other bHLH proteins. First, we observed that DcPAR1-GFP presents nuclear localization in cells of Nicotiana benthamiana leaves (Supplemental Figure 3).…”
Section: Resultsmentioning
confidence: 99%